The Growth Performance of Larasati tilapia (Oreochromis niloticus Linnaeus, 1758) Farming Using Bioflocs Technology - Fajar Basuki; Sri Hastuti; Subandiyono Subandiyono; Wartono Hadie (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
This research was aimed to discover the growth of converted Larasati tilapia (Oreochromis niloticus Linnaeus, 1758) using bioflocs system on its farming, the dynamics of its water quality, and the fish health condition. Bioflocs is the utilization of floc-forming bacteria (flocs forming bacteria) for sewage treatment. Waste mentioned in fish farming is particularly faeces and feed residue. This research took place at Laboratory of Aquaculture, Fisheries Department, Faculty of Fisheries and Marine Science of Diponegoro University. It started from May 2013 to August 2013. The design of the research was exploratory. The data of Larasati tilapia are from Janti, weighted 93.32 g or 200 fish per m3. The fiber tank with 2 m3 capacity is prepared for the bioflocs technique. The result shows that the growth of Larasati tilapia with bioflocs system on its farming is better than with the conventional system. The survival rate SR reaches 90 % and food corvertion ratio FRC reaches 0.82. The water quality shows that there is oxygen dynamics around 4 mg · L–1 to 5 mg · L–1 and Amonia around 0.01 mg · L–1 to 0.015 mg · L–1. Based on the cell concentration and the blood chemistry, it can be concluded that the L. tilapia with bioflocs system on its farming is healthy.